Child Abuse by Teachers and Legal Ways to Encounter in Rural Areas - Shahnaz Rahpaymaelizehee, Mohtaram Rabbani Masoumeh Pourrajab, Bahare Fallahi (Journal of Educational, Health and Community Psychology, 2014)
Â AbstractMany children closely interact with teachers for nine months out of the year and schools are one of the safest places for students to be educated and teachers have a vital role for this education. Teachers should prevent from different kinds of child abuses and have an important role for preventing from child abuse. The primary purpose of this literature review study is to investigate of the phenomenon of child abuse within the school environment by teachers. The second aim of this paper is to determine the legal ways in different countries to encounter with physical child abuse by teachers. Child abuse by teachers has an in depth influence on childrenâs behaviors and their academic achievements. Abused children have been found to suffer from extreme deficits in school, exhibit poor academic performance, antisocial behaviour, poor self-respect, higher criminal behaviour rates, scepticism of adults, and central nervous system functioning. The findings of this paper showed that there are many reported cases of child abuse by teachers in rural areas, nevertheless, many countries banned or restricted physical abuse or corporal punishment and made legal decisions.Key word Legal ways, teachers, child abuse, rural, corporal punishment